2012
DOI: 10.1039/c2cc33203e
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed decarboxylative C(sp2)–C(sp3) coupling reactions via radical mechanism

Abstract: We have successfully developed an example of copper-catalyzed decarboxylative C(sp(2))-C(sp(3)) coupling reactions via C-H functionalization for the first time. It is noteworthy that our catalytic system is very stable, low-cost, palladium-free, ligand-free, and easily accessible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(26 citation statements)
references
References 43 publications
0
25
0
1
Order By: Relevance
“…[1] Their key advantage over traditional cross-coupling reactions is that they draw on stable and readily available carboxylate salts as sources of carbon nucleophiles rather than expensive and sensitive organometallic reagents. In the last decade, a rapidly growing number of decarboxylative reactions have been discovered including decarboxylative Heck reactions, [2] allylations, [3] redox-neutral cross-coupling reactions, [4] oxidative coupling reactions, [5] CÀH arylations, [6] homocouplings, [7] and Chan-Lam-type reactions. [8] Redox-neutral decarboxylative cross-couplings mediated by Cu/Pd or Ag/Pd bimetallic catalyst systems proved to have a particularly broad scope with regards to both carboxylates and carbon electrophiles.…”
mentioning
confidence: 99%
“…[1] Their key advantage over traditional cross-coupling reactions is that they draw on stable and readily available carboxylate salts as sources of carbon nucleophiles rather than expensive and sensitive organometallic reagents. In the last decade, a rapidly growing number of decarboxylative reactions have been discovered including decarboxylative Heck reactions, [2] allylations, [3] redox-neutral cross-coupling reactions, [4] oxidative coupling reactions, [5] CÀH arylations, [6] homocouplings, [7] and Chan-Lam-type reactions. [8] Redox-neutral decarboxylative cross-couplings mediated by Cu/Pd or Ag/Pd bimetallic catalyst systems proved to have a particularly broad scope with regards to both carboxylates and carbon electrophiles.…”
mentioning
confidence: 99%
“…[36] Cinnamic acid undergoes decarboxylative C(sp 2 )ÀC(sp 3 ) coupling with toluene catalyzed by CuO in presence of DTBP. [49] We reported that carboxylic acids reacted with DMF in presence of CuO nanoparticles and TBHP to afford dimethyl substituted amides with 82 % yield and the yields were poor when the reaction was conducted under similar conditions using homogeneous catalysts, CuI, CuCl and CuBr 2 .78 % yield of amide was obtained when the same reaction was conducted on a 10 mmol scale and the CuO nanoparticles are recovered and reused without loss of activity. [50] Benzoic acids and substituted benzoic acids containing electron-rich or electron-deficient groups as well as halogenated carboxylic acids, 4-chlorobenzoic acid, 2-iodobenzoic acid and 3-bromobenzoic acids afforded the corresponding amides in good yields ( Table 2).…”
Section: Amidationmentioning
confidence: 98%
“…Cinnamic acid undergoes decarboxylative C(sp 2 )−C(sp 3 ) coupling with toluene catalyzed by CuO in presence of DTBP . We reported that carboxylic acids reacted with DMF in presence of CuO nanoparticles and TBHP to afford dimethyl substituted amides with 82 % yield and the yields were poor when the reaction was conducted under similar conditions using homogeneous catalysts, CuI, CuCl and CuBr 2 .78 % yield of amide was obtained when the same reaction was conducted on a 10 mmol scale and the CuO nanoparticles are recovered and reused without loss of activity .…”
Section: Coupling Chemistrymentioning
confidence: 99%
See 2 more Smart Citations